An interface-contact regulation renders thermally safe lithium metal batteries - Jiang, Feng-Ni; Yang, Shi-Jie; Cheng, Xin-Bing; Yuan, Hong; Liu, Lei; Huang, Jia-Qi; Zhang, Qiang (eTransportation (Amsterdam), 2023)
The reactions among lithium metal anode, cathode, and electrolyte contribute to the origin of thermal runaway of Li metal batteries (LMBs). In this contribution, polyethylene glycol (PEG) is adopted as an effective thermal safety modifier to reduce the reactions between cell components. The heat release and the initial exothermic peak for cell components mixture can be changed from 26.44 to 10.15 W g−1 and 144 to187 °C with the addition of PEG. The highly viscous PEG leads to the poor contact and reduces reactions between electrolyte and electrodes, thus enhancing the thermal stability of Li metal batteries. Therefore, regulating the contact and reaction interface between electrodes and electrolyte during thermal runaway can be an efficient strategy to design a thermally safe LMBs. This work elucidates the design principles for the interface exothermic reactions during thermal runaway. The contact variation between the electrolytes and electrodes can be regulated by the introduction of polyethylene glycol, which renders to the reduced interfacial exothermic reactions and the improvement in thermal stability of high-energy-density lithium metal batteries. [Display omitted] •Exothermic reactions during LMB thermal runaway are quantitatively investigated.•Functions of PEG on thermal safety of LMBs are explicitly analyzed.•Methods to regulate contact behave between electrode and electrolyte are proposed.